Retrospective analysis of treatment outcomes in polytrauma patients with multiple long bone fractures of lower extremities - Sergii Dubrov; Olexandr Burianov; Taras Omelchenko; Myroslav Vakulych; Dmytro Miasnikov; Volodymyr Lianskorunskyi (Journal of Education, Health and Sport, 2020)
The aim: to conduct retrospective analysis of treatment outcomes in polytrauma patients with multiple long bone fractures of lower extremities. Materials and methods: retrospective study of treatment results in patients hospitalized to the polytrauma department of Kyiv City Clinical Hospital №17 from January 2013 to December 2016. Results: among patients with polytrauma and multiple long bone fractures of lower extremities, males dominated (67.9%) and the main cause of injury was a road accident (73.3%). The most common localizations of injuries were chest trauma (82.4%), traumatic brain injury (74.8%). The severity of injury was 29.2 ± 10.5 points according to the Injury Severity Score (ISS), degree of consciousness disorders was 9.1 ± 3.3 points in conformity with Glasgow Coma Scale (GCS). Patients developed complications, including nosocomial pneumonia (40.5%), acute respiratory distress syndrome (ARDS) (19.1%) and fat embolism syndrome (10.7%), as well as sepsis (28.2%) and multiple organ failure (MOF) (16.0%). Mortality rate was 24.4%. Conclusion: It was found that among patients with polytrauma and multiple long bone fractures of lower extremities males dominated on the basis of gender, the main cause of injury was a road accident. The most common localizations of injuries were chest trauma and traumatic brain injury. Among controversial issues of treatment and diagnostic process are low frequency of pelvic binder application, ultrasound according to focused assessment with sonography for trauma (FAST) protocol and whole body multispiral computed tomography (WBMCT), which should be performed in 100.0% of patients with high-energy trauma at the time of admission to the hospital. In addition, frequency of Early Total Care (ETC) tactics application was too low, and definitive osteosynthesis in some cases was performed unreasonably late, using conservative fixation methods, which is a cause of complications and treatment prolongation in patients with polytrauma. The most common complications were pulmonary: nosocomial pneumonia, ARDS and fat embolism syndrome. Mortality rate was 24.4%.